Adonidia merrillii: Christmas Palm - Timothy K. Broschat (EDIS, 2015)
The Christmas palm (Adonidia merrillii) is a fast-growing palm that is well-suited for small sites, requires little maintenance, is relatively disease-free, and produces clusters of bright red fruit in winter, hence the common name Christmas palm. This revised 2-page fact sheet covers the Christmas palms biology, distribution and habitat, susceptibility to disease, and general care. Written by Timothy K. Broschat, and published by the UF Department of Environmental Horticulture, July 2015.